Efficacy of steroid injection versus physiotherapy treatment in work related trigger finger - Mustapha, Mohd Farid; Khalid, Kamarul Ariffin; Ismail, Raffael; Kassim, KM; Singh, ASJ (2019)
Introduction Stenosing tenosynovitis or trigger finger is a common problem among patients seeking treatment in the orthopaedic clinic. Trigger finger is characterized by locking or painful snapping when flexing the. Multiple approaches can be used to treat a patient with trigger finger. It can be divided into two major groups, either conservative or operative treatment. Conservative treatment varies in modalities. It includes non-steroidal anti-inflammatory drugs, ice packing, extension splint, physiotherapy, or corticosteroid injection. Operative treatment release the annular A1 pulley percutaneously or open.